Pengembangan Media Roda Putar Kebudayaan (Rotan) untuk Pembelajaran Tematik Tema 7 Sub-Tema 2 Kelas IV SDN Inpres 1 Samili - Wulandari, Wulandari; Tati Haryati; Roni Irawan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This objective is to develop valid, practical and effective Rattan media (cultural wheel) in increasing learning motivation of fourth grade students at SDN Inpres Samili. The type of research used by the researcher is R&D (Research & Development) using the ADIE development model (Analysis, Development, Implementation, and Evaluation). In this development research, the effectiveness test was carried out in class V and the practicality test was carried out on fourth grade students at SDN Inpres Samili as a test of practicality and product effectiveness. The results of the study showed that the validity of the Rattan media (cultural wheel) from 4 media and material validators obtained an average score of 93.87 (very valid). The questionnaire response of limited test students showing the practicality of the Rattan media (cultural wheel) obtained an average score of 93.33 (very practical). Thus, the rattan media learning media in sub-theme 2 can be used as a thematic learning media for fourth grade students at SDN Inpres Samili.